“Rainbow Learning Box”: Media dan Alat Pembelajaran Sains Menggunakan Pewarna Warni untuk Menumbuhkan Literasi Sains Anak Usia Dini - Ima Ismail; Wa Ode Rizka Fauziah Ali (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2022)
This study aims to develop and determine the effectiveness of the "Rainbow Learning Box" learning media in fostering scientific literacy in early childhood. This media is designed as a simple, experiment-based science learning tool using colorful colors to help children understand the concepts of color, color mixing, and simple changes through play-and-learning activities. The study employed the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study subjects consisted of 20 children aged 5–6 years at a pre-school (PAUD) institution. Data collection techniques included observation, interviews, documentation, and child development assessment sheets. The results showed that the use of the "Rainbow Learning Box" increased children's engagement in learning, curiosity, observation skills, and simple communication skills related to experimental results. Children appeared more active and enthusiastic during learning activities because the media was engaging, interactive, and suited to the learning characteristics of early childhood. Furthermore, teachers responded positively to the media's use, citing its ease of use, safety, and affordability. Therefore, the "Rainbow Learning Box" can be an alternative, innovative science learning media to optimally support the development of scientific literacy in early childhood.